Control components using Si, GaAs, and GaN technologies - Bahl, Inder J. (Artech House, 2014)
The unique features of this book include in-depth and comprehensive study of control circuits, extensive design equations and figures, treatment of practical aspect of circuits, and description of fabrication technologies.